Hardening composition

A curable composition combining specific ratios of (meth)acrylic acid ester copolymer, polyoxyalkylene polymer, and epoxy resin addresses the issues of weather resistance and flexibility in adhesive materials, offering enhanced durability and appearance for exterior building applications.

JP7619005B2Active Publication Date: 2025-01-22TOAGOSEI CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020185601
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-06
Publication Date
2025-01-22
Estimated Expiration
2040-11-06

AI Technical Summary

Technical Problem

Existing adhesive compositions for building exteriors, particularly those using organic materials, suffer from inadequate weather resistance and flexibility, leading to deterioration and discoloration, while compositions with high adhesive strength often lack flexibility.

Method used

A curable composition comprising a (meth)acrylic acid ester copolymer with 0 to 1.2 crosslinkable silyl groups, a polyoxyalkylene polymer with crosslinkable silyl groups, and an epoxy resin with a bisphenol skeleton, balanced in specific proportions to achieve excellent adhesive strength, flexibility, and weather resistance.

Benefits of technology

The composition provides a balanced performance with high adhesive strength, flexibility, and weather resistance, making it suitable for exterior applications like tiling adhesives, with improved durability and appearance retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619005000001
    Figure 0007619005000001
  • Figure 0007619005000002
    Figure 0007619005000002
  • Figure 0007619005000003
    Figure 0007619005000003
Patent Text Reader

Abstract

To provide a curable composition excellent in adhesive force, flexibility, and weather resistance.SOLUTION: The curable composition contains (A) a (meth)acrylate copolymer having 0-1.2 crosslinkable silyl groups per molecule, (B) a polyoxyalkylene polymer having a crosslinkable silyl group, and (C) an epoxy resin having a bisphenol skeleton. The curable composition contains 20-80 pts.mass of the component (A), 10-75 pts.mass of the component (B), and 5-65 pts.mass of the component (C) (provided that the total of the component (A), the component (B), and the component (C) is 100 pts.mass). The weight average molecular weight (Mw) of the component (A) is preferably 1,000 or more and 50,000 or less. The viscosity of the component (A) at 25°C is preferably 1,000 mPa s or more and 300,000 mPa s or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable composition, and more particularly to a curable composition excellent in adhesive strength, flexibility, and weather resistance, and to the use of the curable composition as an adhesive composition. [Background technology]

[0002] In recent years, adhesives used for tiling building exteriors have been replaced by organic materials, rather than inorganic mortar, due to their ease of application and resistance to peeling. The important properties required for adhesives used on building exteriors are adhesive strength and weather resistance, but organic materials can suffer from deterioration over time, so materials with good weather resistance are required. In particular, in the case of tile adhesives, there are gaps between tiles and they are directly exposed to sunlight, wind and rain, so deterioration and fading can progress, affecting the design of the building. On the other hand, organic materials are flexible and can absorb distortion caused by shocks such as earthquakes, and expansion and contraction over time, helping to prevent peeling.

[0003] Conventionally, Patent Documents 1 and 2 disclose adhesives having high mechanical properties such as adhesive strength, which are obtained by mixing a polyoxyalkylene polymer having a crosslinkable silyl group with an epoxy resin. Patent Documents 3 to 6 disclose compositions comprising a polyoxyalkylene polymer having a crosslinkable silyl group, an acrylic polymer, and an epoxy resin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2000 / 056818 [Patent Document 2] JP 2004-107652 A [Patent Document 3] JP 2003-226854 A [Patent Document 4] International Publication No. 2012 / 121288 [Patent Document 5] JP 2019-143014 A [Patent Document 6] JP 2019-143116 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the compositions of Patent Documents 1 to 3 have insufficient weather resistance. The composition of Patent Document 4 lacks flexibility, and the compositions of Patent Documents 5 and 6 have problems in that they have insufficient adhesive strength.

[0006] An object of the present invention is to provide a curable composition having excellent adhesive strength, flexibility and weather resistance. [Means for solving the problem]

[0007] As a result of intensive research aimed at solving the above problems, the present inventors have found that in a composition containing a polyoxyalkylene polymer having a crosslinkable silyl group, an acrylic polymer, and an epoxy resin, it is possible to achieve a balance between adhesive strength, flexibility, and weather resistance by blending these three components in a well-balanced manner, and further, it is possible to further improve flexibility by setting the number of crosslinkable silyl groups in the acrylic polymer to a certain value or less, thereby completing the present invention.

[0008] Thus, according to one aspect, the present invention provides a method for producing a method for treating a pulmonary circulation comprising the steps of: (A) a (meth)acrylic acid ester copolymer having 0 to 1.2 crosslinkable silyl groups per molecule, (B) a polyoxyalkylene polymer having a crosslinkable silyl group, and (C) an epoxy resin having a bisphenol skeleton, The curable composition includes 20 to 80 parts by mass of the component (A), 10 to 75 parts by mass of the component (B), and 5 to 65 parts by mass of the component (C) (the total of the components (A), (B), and (C) is 100 parts by mass).

[0009] According to still another aspect, the present invention provides an adhesive composition comprising the curable composition of the present invention. Effect of the Invention

[0010] According to the present invention, a composition is prepared by blending 20 to 80 parts by mass of component (A), 10 to 75 parts by mass of component (B), and 5 to 65 parts by mass of component (C) (wherein the total of components (A), (B), and (C) is 100 parts by mass), so that a curable composition having an excellent balance of adhesive strength, flexibility, and weather resistance can be obtained. Therefore, the curable composition can be suitably used as an adhesive for building exteriors, in particular, as an adhesive for exterior tiling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. In the present invention, "(meth)acrylate" means either or both of acrylate and methacrylate, "(meth)acrylic" means either or both of acrylic and methacrylic, and "(meth)acryloyl" means either or both of acryloyl and methacryloyl.

[0012] <Component (A): (meth)acrylic acid ester copolymer> The (meth)acrylic acid ester copolymer (A) (sometimes referred to as "component (A)" in this specification) is a polymer having a structural unit derived from a (meth)acrylic acid ester monomer, and can be obtained, for example, by polymerizing a monomer mixture containing a (meth)acrylic acid ester monomer. Examples of the (meth)acrylic acid ester monomer include (meth)acrylic acid alkyl ester and (meth)acrylic acid alkoxyalkyl ester. The amount of the (meth)acrylic acid ester monomer used is preferably in the range of 10 to 100% by mass, more preferably in the range of 30 to 100% by mass, and even more preferably in the range of 50 to 100% by mass, based on the total constituent monomers of the (meth)acrylic acid ester copolymer.

[0013] Specific examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. xyl, n-nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosyl (meth)acrylate, behenyl (meth)acrylate, tetracosyl (meth)acrylate, (meth) Hexacosyl acrylate, octacosyl (meth)acrylate, triacontyl (meth)acrylate, dotriacontyl (meth)acrylate, tetratriacontyl (meth)acrylate, hexatriacontyl (meth)acrylate, octatriacontyl (meth)acrylate, tetracontyl (meth)acrylate, isodecyl (meth)acrylate, isoundecyl (meth)acrylate, isolauryl (meth)acrylate, isotridecyl (meth)acrylate, isotetradecyl (meth)acrylate, isopentadecyl (meth)acrylate, (meth)acrylic isohexadecyl (meth)acrylate, isoheptadecyl (meth)acrylate, isostearyl (meth)acrylate, isononadecyl (meth)acrylate, isoeicosyl (meth)acrylate, isoheneicosyl (meth)acrylate, isobehenyl (meth)acrylate, isotetracosyl (meth)acrylate, isohexacosyl (meth)acrylate, isooctacosyl (meth)acrylate, isotriacontyl (meth)acrylate, isodotriacontyl (meth)acrylate, isotetratriacontyl (meth)acrylate, isohexatriacontyl (meth)acrylate,Examples include (meth)acrylic acid alkyl esters having a linear or branched aliphatic alkyl group or an alicyclic alkyl group, such as isooctatriacontyl (meth)acrylate and isotetracontyl (meth)acrylate, and one or more of these can be used. Among these, from the viewpoint of the mechanical properties of the cured product, (meth)acrylic acid alkyl esters having an alkyl group with 1 to 8 carbon atoms are preferred. The amount of (meth)acrylic acid alkyl esters having an alkyl group with 1 to 8 carbon atoms used is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more, based on the total constituent monomers of the (meth)acrylic acid ester copolymer. The upper limit is 100% by mass, and may be 90% by mass, 80% by mass, or 50% by mass.

[0014] Among the above, the use of an alkyl (meth)acrylate having an alkyl group having 10 or more carbon atoms is preferable in that good compatibility with the polyoxyalkylene polymer is ensured and mechanical properties and weather resistance are good. The number of carbon atoms in the alkyl group is preferably 10 to 20, more preferably 12 to 20. The amount of the alkyl (meth)acrylate having an alkyl group having 10 or more carbon atoms used is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, based on the total constituent monomers of the (meth)acrylic acid ester copolymer. The upper limit is 100% by mass or less, and may be 90% by mass or less, 80% by mass or less, or 50% by mass or less.

[0015] Specific examples of the (meth)acrylic acid alkoxyalkyl ester include methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, methoxybutyl (meth)acrylate, methoxyhexyl (meth)acrylate, ethoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, ethoxybutyl (meth)acrylate, ethoxyhexyl (meth)acrylate, butoxymethyl (meth)acrylate, butoxyethyl (meth)acrylate, butoxybutyl (meth)acrylate, and butoxyhexyl (meth)acrylate, and one or more of these can be used. Among these, from the viewpoint of mechanical properties of the cured product, (meth)acrylic acid alkoxyalkyl esters having an alkoxyalkyl group with 2 to 8 carbon atoms are preferred, and (meth)acrylic acid alkoxyalkyl esters having an alkoxyalkyl group with 2 to 4 carbon atoms are more preferred. The amount of (meth)acrylic acid alkoxyalkyl ester used is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more, based on the total constituent monomers of the (meth)acrylic acid ester copolymer. The upper limit is 100% by mass or less, and may be 90% by mass or less, 80% by mass or less, or 50% by mass or less.

[0016] The (meth)acrylic acid ester copolymer may have a crosslinkable silyl group in the molecule. When the (meth)acrylic acid ester copolymer has a crosslinkable silyl group, the mechanical properties of the cured product tend to be good. The type of the crosslinkable silyl group is not particularly limited, and examples thereof include an alkoxysilyl group, a halogenosilyl group, and a silanol group, but an alkoxysilyl group is preferred from the viewpoint of easy control of reactivity. Specific examples of the alkoxysilyl group include trialkoxysilyl groups such as a trimethoxysilyl group, a triethoxysilyl group, a dimethoxyethoxysilyl group, and a methoxydiethoxysilyl group; dialkoxysilyl groups such as a methyldimethoxysilyl group, a methyldiethoxysilyl group, an ethyldimethoxysilyl group, and an ethyldiethoxysilyl group; and monoalkoxysilyl groups such as a dimethylmethoxysilyl group, a dimethylethoxysilyl group, a diethylmethoxysilyl group, and a diethylethoxysilyl group. Of these, dialkoxysilyl groups and trialkoxysilyl groups are preferred, trialkoxysilyl groups are more preferred, and trimethoxysilyl groups are particularly preferred.

[0017] In the present invention, the number of crosslinkable silyl groups per molecule of the (meth)acrylic acid ester copolymer (A) is 0 to 1.2, and it is preferable that the number of crosslinkable silyl groups is 0, that is, that the copolymer has no crosslinkable silyl groups. Note that the number of crosslinkable silyl groups means the average number of crosslinkable silyl groups contained in one polymer molecule of the component (A). When component (A) has a crosslinkable silyl group, the number of the crosslinkable silyl group is 1.2 or less, so that the flexibility of the cured product is excellent.The upper limit of the number of the crosslinkable silyl group is preferably 1.0 or less, more preferably 0.8 or less, even more preferably 0.6 or less, and particularly preferably 0.3 or less.In addition, when the number of the crosslinkable silyl group is 0.05 or more, the weather resistance is improved, more preferably 0.1 or more, and even more preferably 0.02 or more. The position of the crosslinkable silyl group contained in the (meth)acrylic acid ester copolymer is not particularly limited, and it may be located in a side chain and / or at the end of the polymer.

[0018] The crosslinkable silyl group can be obtained, for example, by polymerizing a monomer mixture containing a (meth)acrylic acid ester monomer and a vinyl monomer having a crosslinkable silyl group. Examples of vinyl monomers having a crosslinkable silyl group include vinyl silanes such as vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, and vinyldimethylmethoxysilane; silyl group-containing (meth)acrylic acid esters such as trimethoxysilylpropyl (meth)acrylate, triethoxysilylpropyl (meth)acrylate, dimethylmethoxysilylpropyl (meth)acrylate, and methyldimethoxysilylpropyl (meth)acrylate; silyl group-containing vinyl ethers such as trimethoxysilylpropyl vinyl ether; and silyl group-containing vinyl esters such as vinyl trimethoxysilylundecanoate. One or more of these may be used.

[0019] The (meth)acrylic acid ester copolymer may be prepared by copolymerizing, in addition to the above-mentioned monomers, other monomers copolymerizable therewith. Examples of the other monomers include functional group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate, and ethylene oxide adducts of (meth)acrylic acid; (meth)acrylic acid aromatic esters such as phenyl (meth)acrylate, toluyl (meth)acrylate, and benzyl (meth)acrylate; Fluorine-containing (meth)acrylic acid esters such as trifluoromethylmethyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethylmethyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethylmethyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, and 2-perfluorohexadecylethyl (meth)acrylate; Fluorine-containing olefins such as perfluoroethylene, perfluoropropylene, and vinylidene fluoride Aromatic monomers such as styrene, vinyltoluene, α-methylstyrene, chlorostyrene, styrenesulfonic acid and its salts; Maleic anhydride; unsaturated dicarboxylic acids such as maleic acid and fumaric acid, and their mono- and dialkyl esters; Maleimide compounds such as maleimide, methylmaleimide, ethylmaleimide, propylmaleimide, butylmaleimide, hexylmaleimide, octylmaleimide, phenylmaleimide, and cyclohexylmaleimide; Nitrile group-containing vinyl monomers such as acrylonitrile and methacrylonitrile; Amide group-containing vinyl monomers such as acrylamide and methacrylamide; Vinyl esters such as vinyl acetate, vinyl propionate, vinyl pivalate, vinyl benzoate, and vinyl cinnamate; Alkenes such as ethylene and propylene; Conjugated dienes such as butadiene and isoprene; Examples of the vinyl chloride include, but are not limited to, vinyl chloride, vinylidene chloride, allyl chloride, allyl alcohol, etc. Furthermore, one or more of these may be used.

[0020] The weight average molecular weight (Mw) of the (meth)acrylic acid ester copolymer is a polystyrene-equivalent molecular weight by gel permeation chromatography (hereinafter also referred to as "GPC"), and is preferably 1,000 or more, more preferably 2,000 or more, and even more preferably 3,000 or more from the viewpoint of weather resistance of the cured product. On the other hand, from the viewpoint of workability (low viscosity), the upper limit of Mw is preferably 50,000 or less, more preferably 30,000 or less, even more preferably 20,000 or less, and even more preferably 10,000 or less. The range of Mw can be set by combining the above upper and lower limits, and may be, for example, 1,000 or more and 50,000 or less, 2,000 or more and 30,000 or less, or 3,000 or more and 20,000 or less.

[0021] The molecular weight distribution of the (meth)acrylic acid ester copolymer is calculated as the value (Mw / Mn) obtained by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn). From the viewpoint of the balance between tensile properties and workability, Mw / Mn is preferably 5.0 or less, more preferably 4.0 or less, even more preferably 3.0 or less, and even more preferably 2.5 or less. The lower limit of Mw / Mn is usually 1.0.

[0022] The viscosity of the (meth)acrylic acid ester copolymer at 25°C is preferably 1,000 mPa·s or more, more preferably 2,000 mPa·s or more. The viscosity may be 3,000 mPa·s or more, 5,000 mPa·s or more, or 10,000 mPa·s or more. The upper limit of the viscosity is preferably 300,000 mPa·s or less, more preferably 180,000 mPa·s or less, even more preferably 100,000 or less, and even more preferably 60,000 mPa·s or less. If the viscosity is 1,000 mPa·s or more, sagging when applied to a vertical surface is suppressed, and by making the viscosity 300,000 mPa·s or less, the workability of the curable composition is improved. The viscosity range can be set by combining the above upper and lower limits, and may be, for example, 1,000 mPa·s or more and 300,000 mPa·s or less, such as 2,000 mPa·s or more and 180,000 mPa·s or less, or 3,000 mPa·s or more and 60,000 mPa·s or less.

[0023] In the present invention, the (meth)acrylic acid ester copolymer may have a double bond in the molecule. If the (meth)acrylic acid ester copolymer has an appropriate amount of double bonds, the double bonds react during the period when the cured product is exposed to outdoors, etc., and the molecular weight is increased appropriately, thereby improving weather resistance. Therefore, in the present invention, the viscosity of the (meth)acrylic acid ester copolymer is suppressed to ensure workability, and the cured product can exhibit excellent weather resistance. Note that the above mechanism is speculation and does not limit the scope of the present invention.

[0024] There is no particular limitation on the method for introducing the double bond, and any method known to those skilled in the art can be used. For example, there is a method of copolymerizing a monomer having a plurality of double bonds in the molecule, or a method of producing a (meth)acrylic acid ester copolymer having a functional group, and then reacting the copolymer with a compound having a functional group and a double bond that can react with the functional group.

[0025] Also, double bonds can be introduced by carrying out the production of a (meth)acrylic acid-based polymer under high temperature conditions. For example, if the polymerization temperature is 100°C or higher, a cleavage reaction that begins with a hydrogen abstraction reaction from a polymer chain occurs due to high-temperature polymerization, and a polymer having an ethylenically unsaturated bond represented by the following general formula (1) at the molecular end is obtained. The polymerization temperature is preferably 120°C or higher, more preferably 150°C or higher. The higher the polymerization temperature, the higher the double bond concentration in the polymer tends to be. According to the above method, a (meth)acrylic acid ester copolymer having double bonds can be obtained simply and with good productivity. Furthermore, it is possible to easily produce the copolymer without containing a large amount of impurities such as initiators and chain transfer agents for molecular weight control. It is preferable not to use chain transfer agents such as mercaptans, as they lead to a decrease in weather resistance. On the other hand, it is preferable to set the upper limit of the polymerization temperature to 350°C or lower in order to eliminate the risk of coloring of the polymerization solution or a decrease in molecular weight due to a decomposition reaction. By carrying out polymerization within the above temperature range, a copolymer having an appropriate molecular weight, low viscosity, no coloring, and few impurities can be efficiently produced. That is, according to this polymerization method, it is possible to use only a very small amount of a polymerization initiator, and it is not necessary to use a chain transfer agent such as mercaptan or a polymerization solvent, and it is possible to obtain a copolymer with high purity.

[0026] [ka] [In the formula, M represents a monomer unit, and n is a natural number representing the degree of polymerization. 1 represents a monovalent organic group.

[0027] R in the above general formula (1) 1 is an alkyl group, a hydroxyalkyl group, an alkoxyalkyl group, an alkyl group which may have other substituents, a phenyl group, a benzyl group, a polyalkylene glycol group, a dialkylaminoalkyl group, a trialkoxysilylalkyl group, an alkyldialkoxysilylalkyl group, or a hydrogen atom.

[0028] The (meth)acrylic acid ester copolymer can be produced by normal radical polymerization. Any of solution polymerization, bulk polymerization, and dispersion polymerization may be adopted, and a living radical polymerization method may also be utilized. The reaction process may be any of batch, semi-batch, and continuous polymerization methods. Among these, a high-temperature continuous polymerization method at 100 to 350°C is preferred.

[0029] In general, when crosslinkable functional groups are uniformly introduced into a polymer, the curability of a curable composition containing the polymer and the physical properties such as weather resistance of the resulting cured product are good. In this respect, it is preferable to use a stirred tank reactor as the reactor, since it is possible to obtain a (meth)acrylic acid ester copolymer with a relatively narrow composition distribution (distribution of crosslinkable functional groups) and molecular weight distribution. In addition, a process using a continuous stirred tank reactor is more preferable in terms of narrowing the composition distribution and molecular weight distribution.

[0030] The high-temperature continuous polymerization method may be performed according to known methods disclosed in JP-A-57-502171, JP-A-59-6207, JP-A-60-215007, etc. For example, a pressurizable reactor is filled with a solvent, and a predetermined temperature is set under pressure, and then a monomer mixture consisting of each monomer and, if necessary, a polymerization solvent is fed to the reactor at a constant feed rate, and an amount of polymerization liquid corresponding to the amount of the monomer mixture fed is extracted. In addition, a polymerization initiator may be blended into the monomer mixture as necessary. The blending amount in this case is preferably 0.001 to 2 parts by mass per 100 parts by mass of the monomer mixture. The pressure depends on the reaction temperature and the boiling points of the monomer mixture and solvent used, and does not affect the reaction, but may be a pressure that can maintain the reaction temperature. The residence time of the monomer mixture is preferably 1 to 60 minutes. If the residence time is less than 1 minute, the monomer may not react sufficiently, and if the unreacted monomer exceeds 60 minutes, the productivity may decrease. The preferred residence time is 2 to 40 minutes.

[0031] Examples of the polymerization initiator used to obtain the (meth)acrylic acid ester copolymer may be any initiator that generates radicals at a predetermined reaction temperature. Specific examples include organic peroxides such as di-t-butyl peroxide, di-t-hexyl peroxide, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, cumene hydroperoxide, and t-butyl hydroperoxide, and azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), azobiscyclohexacarbonitrile, azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-amidinopropane)dihydrochloride, and 4,4'-azobis(4-cyanovaleric acid). The polymerization initiator may be used alone or in combination of two or more of these. When a polymerization initiator having a high hydrogen abstraction ability is used, the double bond concentration of the resulting polymer tends to be high. For example, the use of an organic peroxide rather than an azo compound tends to give a polymer having a high double bond concentration. The amount of the polymerization initiator used can be appropriately adjusted depending on the type of polymerization initiator and monomer, the desired molecular weight, polymerization conditions, etc., but is generally 0.001 to 10 parts by mass per 100 parts by mass of the monomer used. When a polymer of the same molecular weight is obtained, the double bond concentration in the obtained polymer tends to be higher as the amount of the polymerization initiator used is smaller.

[0032] When an organic solvent is used for the production of the (meth)acrylic acid ester copolymer, an organic hydrocarbon compound is suitable, and examples thereof include cyclic ethers such as tetrahydrofuran and dioxane, aromatic hydrocarbon compounds such as benzene, toluene and xylene, esters such as ethyl acetate and butyl acetate, ketones such as acetone, methyl ethyl ketone and cyclohexanone, and alcohols such as methanol, ethanol and isopropanol, and one or more of these can be used. If the solvent does not dissolve the (meth)acrylic acid ester copolymer well, scale tends to grow on the wall of the reactor, which can cause production problems in the cleaning process. In addition, when an organic solvent with high chain transfer ability such as isopropanol is used, the double bond concentration in the obtained polymer tends to be low. The amount of the solvent used is preferably 80 parts by mass or less relative to 100 parts by mass of the total vinyl monomers. By using 80 parts by mass or less, a high conversion rate can be obtained in a short time. More preferably, the amount is 1 to 50 parts by mass. In addition, a dehydrating agent such as trimethyl orthoacetate or trimethyl orthoformate can also be added.

[0033] A known chain transfer agent may be used in the production of the (meth)acrylic acid ester copolymer. When a chain transfer agent is used, the double bond concentration in the resulting polymer tends to be low. In addition, the double bond concentration generally decreases as the amount of the chain transfer agent used increases.

[0034] The reaction liquid discharged from the reactor can be directly used for the next step, or the polymer can be isolated by removing volatile components such as unreacted monomers, solvent, and low molecular weight oligomers by distillation, etc. A part of the volatile components such as unreacted monomers, solvent, and low molecular weight oligomers distilled off from the reaction liquid can be returned to the raw material tank or directly to the reactor, and can be reused in the polymerization reaction. Recycling the unreacted monomers and the solvent is an economically preferable method. When recycling, it is necessary to determine the mixing ratio of the monomer mixture to be newly fed so as to maintain the desired monomer ratio and the desired amount of the solvent in the reactor.

[0035] The amount of double bonds introduced into the polymer can be reduced by adding a radical generator and performing post-treatment under heating conditions. The amount of the radical generator added is about 0.1 to 10 parts by mass per 100 parts by mass of the polymer, and the greater the amount added, the greater the effect of reducing the double bond concentration. The heating temperature during the heat treatment is about 50 to 130° C., but the lower the temperature, the greater the effect of reducing the double bond concentration. The heating temperature is preferably in the range of 50 to 110° C., and more preferably in the range of 50 to 100° C. The heat treatment time is not particularly limited, but is preferably set so that the amount of the remaining radical generator is less than 1% by mass relative to the polymer. Those skilled in the art can calculate the amount of the remaining radicals from the activation energy, frequency factor, and reaction temperature of the radical generator used.

[0036] The double bond concentration can also be reduced by subjecting the (meth)acrylic acid ester copolymer to hydrogenation as a post-treatment. For the hydrogenation, a conventionally known method can be used. That is, after adding a homogeneous catalyst or a heterogeneous catalyst to the polymer reaction liquid, the system is put into a hydrogen atmosphere, the pressure is normal pressure to 10 MPa, the temperature is heated to about 20 to 180 ° C, and the reaction is carried out for about 2 to 20 hours. Specific examples of homogeneous catalysts include rhodium complexes such as chlorotris (triphenylphosphine) rhodium, ruthenium complexes such as dichlorotris (triphenylphosphine) ruthenium and chlorohydrocarbonyltris (triphenylphosphine) ruthenium, platinum complexes such as dichlorobis (triphenylphosphine) platinum, and iridium complexes such as carbonylbis (triphenylphosphine) iridium. On the other hand, examples of heterogeneous catalysts include solid catalysts in which transition metals such as nickel, rhodium, ruthenium, palladium, and platinum are supported on carbon, silica, alumina, fibers, organic gel-like materials, etc. Heterogeneous catalysts are preferable in that the catalyst can be easily removed by filtration, etc., so that the quality is stable and expensive catalysts can be reused. The amount of catalyst added is about 10 to 1,000 ppm relative to the vinyl polymer in the case of a homogeneous catalyst, and about 1,000 to 10,000 ppm in the case of a heterogeneous catalyst.

[0037] <Component (B): Polyoxyalkylene polymer having crosslinkable silyl groups> The polyoxyalkylene polymer (B) having a crosslinkable silyl group (sometimes referred to as "component (B)" in this specification) is not particularly limited as long as it contains a repeating unit represented by the following general formula (2). -OR 2 - (2) (In the formula, R 2 is a divalent hydrocarbon group. R in the above general formula (2) 2 Examples of such methods include the following: (CH2) n (n is an integer between 1 and 10) CH(CH3)CH2 CH(C2H5)CH2 C(CH3)2CH2 The polyoxyalkylene polymer may contain one or a combination of two or more of the repeating units described above. Among these, CH(CH3)CH2 is preferred from the viewpoint of excellent workability.

[0038] The crosslinkable silyl group contained in the polyoxyalkylene polymer containing the crosslinkable silyl group is not particularly limited, and may be an alkoxysilyl group, a halogenosilyl group, a silanol group, etc., but an alkoxysilyl group is preferred from the viewpoint of easy control of reactivity. Specific examples of the alkoxysilyl group include a trimethoxysilyl group, a methyldimethoxysilyl group, a dimethylmethoxysilyl group, a triethoxysilyl group, a methyldiethoxysilyl group, a dimethylethoxysilyl group, etc.

[0039] The method for producing a polyoxyalkylene polymer is not particularly limited, and examples thereof include a polymerization method using an alkali catalyst such as KOH, a polymerization method using a transition metal compound-porphyrin complex catalyst, a polymerization method using a composite metal cyanide complex catalyst, and a polymerization method using phosphazene, using a corresponding epoxy compound or diol as a raw material. The polyoxyalkylene polymer may be either a linear polymer or a branched polymer, or a combination of these may be used.

[0040] The average number of crosslinkable silyl groups contained in one molecule of the polyoxyalkylene polymer is preferably in the range of 1 to 4, and more preferably in the range of 1.5 to 3, from the viewpoint of performance such as adhesiveness and tensile properties of the cured product. The position of the crosslinkable silyl group contained in the polyoxyalkylene polymer is not particularly limited, and it may be located in a side chain and / or at the end of the polymer. The polyoxyalkylene polymer may be either a linear polymer or a branched polymer, or a combination of these may be used.

[0041] The number average molecular weight (Mn) of the polyoxyalkylene polymer having a crosslinkable silyl group is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 15,000 or more, from the viewpoint of mechanical properties. Therefore, Mn may be 18,000, 22,000, or 25,000. The upper limit of Mn is preferably 60,000 or less, more preferably 50,000 or less, even more preferably 40,000 or less, and particularly preferably 25,000 or less, from the viewpoint of workability (viscosity) during application of the curable composition. The range of Mn can be set by combining the above upper limit and lower limit, and may be, for example, 5,000 or more and 60,000 or less, 15,000 or more and 60,000 or less, 15,000 or more and 50,000 or less, or 15,000 or more and 25,000 or less.

[0042] Commercially available products may be used as the polyoxyalkylene polymer having a crosslinkable silyl group. Specific examples include "MS Polymer S203", "MS Polymer S303", "MS Polymer S810", "Silyl SAT200", "Silyl SAT350", "Silyl EST280" and "Silyl SAT30" manufactured by Kaneka Corporation, and "Exestar ES-S2410", "Exestar ES-S2420" and "Exestar ES-S3430" (all trade names) manufactured by Asahi Glass Co., Ltd.

[0043] <Component (C): Epoxy resin having a bisphenol skeleton> Examples of the epoxy resin (C) having a bisphenol skeleton (sometimes referred to as "component (C)" in this specification) include epichlorohydrin-bisphenol A type epoxy resins and epichlorohydrin-bisphenol F type epoxy resins. Commercially available epichlorohydrin-bisphenol A type epoxy resins may be used, and specific examples include jER825, 827, 828, 828EL, 828US, 834, 1001, 1003, and 1007 (manufactured by Mitsubishi Chemical Corporation), Epicron 840, 840-S, 850, 850-S, 860, 1050, 1055, 3050, 4050, and 7050 (manufactured by DIC Corporation), and Adeka Resin EP-4100, 4100TX, and 4400 (manufactured by ADEKA Corporation). Similarly, commercially available epichlorohydrin-bisphenol F type epoxy resins may be used. Specific examples include jER806, 806H, and 807 (manufactured by Mitsubishi Chemical Corporation), Epiclon 830, 830-S, and 835 (manufactured by DIC Corporation), and ADEKA RESIN EP-4901 (manufactured by ADEKA Corporation).

[0044] In the present invention, in addition to the epoxy resin (C) having a bisphenol skeleton, other epoxy resins can be used in combination within the scope of not impairing the effects of the present invention. Examples of such other epoxy resins include flame-retardant epoxy resins such as glycidyl ether of tetrabromobisphenol A, glycidyl ether of polyhydric alcohols such as glycerin, and epoxidized products of unsaturated polymers such as petroleum resins, but are not limited thereto.

[0045] Component (C) is preferably used in combination with a curing agent for the epoxy resin. Examples of the curing agent for the epoxy resin include primary amines such as ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine, diethylaminopropylamine, N-aminoethylpiperazine, isophoronediamine, diaminodicyclohexylmethane, m-xylenediamine, m-phenylenediamine, diaminodiphenylmethane, and diaminodiphenylsulfone; (CH3)2N(CH2) nLinear diamines represented by the formula N(CH3)2 (wherein n is an integer of 1 to 10), (CH3)2-N(CH2) n Linear tertiary amines represented by -CH3 (wherein n is an integer from 0 to 10), tetramethylguanidine, alkyl tertiary monoamines represented by N{(CH2)nCH3}3 (wherein n is an integer from 1 to 10), triethanolamine, piperidine, N,N'-dimethylpiperazine, triethylenediamine, pyridine, picoline, diazabicycloundecene, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, 2,4,6-tris(dimethylaminomethyl)phenol, Lamiron C-260 manufactured by BASF, and Araldit manufactured by CIBA Examples of the curable composition include secondary or tertiary amines such as HY-964 and Rohm and Haas's Menthene Diamine, ketimines such as 1,2-ethylenebis(isopentylideneimine), 1,2-hexylenebis(isopentylideneimine), 1,2-propylenebis(isopentylideneimine), p,p'-biphenylenebis(isopentylideneimine), 1,2-ethylenebis(isopropylideneimine), 1,3-propylenebis(isopropylideneimine), and p-phenylenebis(isopentylideneimine), acid anhydrides such as phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic anhydride, various polyamide resins, dicyandiamide and its derivatives, and various imidazoles. In particular, when the curable composition of the present invention is a one-component type curable composition, a ketimine compound that is a latent curing agent can be used. Specific examples of the ketimine compound include jER Cure H3 and H30 (manufactured by Mitsubishi Chemical Corporation), and also include Sila Ace S340 (manufactured by JNC Corporation), which is a ketimine silane compound. The amount of such a curing agent used is preferably 5 parts by mass to 100 parts by mass relative to 100 parts by mass of the epoxy resin.

[0046] Since the adhesive composition provided by the present invention has a crosslinkable silyl group, the strength of the cured adhesive composition can be improved by adding a compound having a group capable of reacting with both a crosslinkable silyl group and an epoxy group. Specific examples of the compound having a group capable of reacting with both a crosslinkable silyl group and an epoxy group include N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.

[0047] <Curable composition> As described above, the curable composition of the present invention is one that contains the components (A), (B) and (C) as essential components. Here, in order to obtain a good balance between the adhesive strength, flexibility and weather resistance of the cured product, it is necessary to blend the components (A) in the range of 20 to 80 parts by mass, the components (B) in the range of 10 to 75 parts by mass and the components (C) in the range of 5 to 65 parts by mass, with the total of the components (A), (B) and (C) being 100 parts by mass. The curable composition of the present invention exhibits excellent weather resistance when the component (A) is 20 parts by mass or more, and exhibits excellent adhesive strength when the component (A) is 80 parts by mass or less. In addition, the curable composition of the present invention exhibits excellent flexibility (elongation of the cured product) when the component (B) is 10 parts by mass or more, and exhibits excellent weather resistance and adhesive strength when the component (B) is 80 parts by mass or less. In addition, the curable composition of the present invention exhibits excellent adhesive strength when the component (C) is 5 parts by mass or more, and exhibits excellent flexibility and weather resistance when the component (C) is 65 parts by mass or less. The amounts of the above three components in the curable composition of the present invention, relative to 100 parts by mass of the total of components (A), (B), and (C), are preferably 20 to 75 parts by mass of component (A), 20 to 75 parts by mass of component (B), and 5 to 60 parts by mass of component (C), more preferably 30 to 70 parts by mass of component (A), 20 to 60 parts by mass of component (B), and 5 to 40 parts by mass of component (C), and even more preferably 45 to 65 parts by mass of component (A), 25 to 50 parts by mass of component (B), and 5 to 20 parts by mass of component (C).

[0048] The curable composition of the present invention may contain components other than the components (A), (B), and (C) so long as the effects of the present invention are not hindered. Such components include fillers, plasticizers, antioxidants, curing accelerators, anti-tack agents, adhesion promoters, etc.

[0049] Examples of fillers include light calcium carbonate with an average particle size of about 0.02 to 2.0 μm, heavy calcium carbonate with an average particle size of about 1.0 to 5.0 μm, titanium oxide, carbon black, synthetic silicic acid, talc, zeolite, mica, silica, calcined clay, kaolin, bentonite, aluminum hydroxide, barium sulfate, glass balloons, silica balloons, and polymethyl methacrylate balloons. These fillers can improve the mechanical properties of the cured product, and can increase its strength and elongation. Among these, light calcium carbonate, heavy calcium carbonate and titanium oxide, which are highly effective in improving physical properties, are preferred, and a mixture of light calcium carbonate and heavy calcium carbonate is more preferred. The amount of the filler added is preferably 20 to 300 parts by mass, and more preferably 50 to 200 parts by mass, relative to 100 parts by mass of the total amount of components (A), (B) and (C). In the case of a mixture of light calcium carbonate and heavy calcium carbonate as described above, the mass ratio of light calcium carbonate / heavy calcium carbonate is preferably in the range of 90 / 10 to 30 / 70.

[0050] Examples of the plasticizer include liquid polyurethane resin, polyester-based plasticizers obtained from dicarboxylic acid and diol; etherified or esterified polyalkylene glycols such as polyethylene glycol and polypropylene glycol; polyether-based plasticizers such as saccharide-based polyethers obtained by addition polymerization of alkylene oxides such as ethylene oxide and propylene oxide to saccharide polyhydric alcohols such as sucrose, followed by etherification or esterification; polystyrene-based plasticizers such as poly-α-methylstyrene; and poly(meth)acrylates having no crosslinkable functional groups. Among these, poly(meth)acrylates having no crosslinkable functional groups are preferred in terms of durability such as weather resistance of the cured product. Among these, those having Mw in the range of 1,000 to 7,000 and glass transition temperature of -30°C or less are more preferred.

[0051] The amount of the plasticizer used in the curable composition is preferably in the range of 0 to 100 parts by mass, may be in the range of 0 to 80 parts by mass, or may be in the range of 0 to 50 parts by mass, assuming that the total amount including components (A), (B), and (C) is 100 parts by mass.

[0052] As the age resistor, usable are ultraviolet absorbers such as benzophenone-based compounds, benzotriazole-based compounds, and anilide oxalate-based compounds, light stabilizers such as hindered amine-based compounds, antioxidants such as hindered phenol-based compounds, heat stabilizers, and age resistors which are mixtures of these. Examples of ultraviolet absorbers include BASF's Tinuvin 571, Tinuvin 1130, and Tinuvin 327. Examples of light stabilizers include BASF's Tinuvin 292, Tinuvin 144, and Tinuvin 123, and Sankyo's Sanol 770. Examples of heat stabilizers include BASF's Irganox 1135, Irganox 1520, and Irganox 1330. BASF's Tinuvin B75, a mixture of ultraviolet absorber, light stabilizer, and heat stabilizer, may also be used.

[0053] As the curing accelerator, known compounds such as tin-based catalysts, titanium-based catalysts and tertiary amines can be used. Examples of tin-based catalysts include dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diacetonate, dioctyltin dilaurate, etc. Specific examples include products sold by Nitto Kasei Corporation under the trade names "Neostan U-28", "Neostan U-100", "Neostan U-200", "Neostan U-220H", "Neostan U-303", and "SCAT-24". Examples of titanium catalysts include tetraisopropyl titanate, tetra-n-butyl titanate, titanium acetylacetonate, titanium tetraacetylacetonate, titanium ethyl acetylacetonate, dibutoxytitanium diacetylacetonate, diisopropoxytitanium diacetylacetonate, titanium octylene glycolate, and titanium lactate. Examples of tertiary amines include triethylamine, tributylamine, triethylenediamine, hexamethylenetetramine, 1,8-diazabicyclo[5,4,0]undecene-7 (DBU), diazabicyclononene (DBN), N-methylmorpholine, and N-ethylmorpholine.

[0054] The amount of the curing accelerator used is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 2 parts by mass, based on 100 parts by mass of the total of components (A), (B) and (C).

[0055] Examples of anti-tack agents include acrylic oligomers such as "Aronix M8030", "M8100", and "M309" manufactured by Toagosei Co., Ltd., or mixtures with photopolymerization initiators, saturated fatty acid oils such as tung oil and linseed oil, "R15HT" manufactured by Idemitsu Sekiyu Co., Ltd., "PBB3000" manufactured by Nippon Soda Co., Ltd., and "Goselaq 500B" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.

[0056] Examples of adhesion promoters include aminosilanes such as those available from Shin-Etsu Silicones under the trade names "KBM602", "KBM603", "KBE602", "KBE603", "KBM902" and "KBM903". In addition, dehydrating agents such as methyl orthoformate, methyl orthoacetate, and vinylsilane, organic solvents, etc. may be added.

[0057] The curable composition can be suitably used as an adhesive. In the field of adhesives for building materials, high weather resistance and durability guaranteed for 10 years or more are required, and the adhesive composition of the present invention can satisfy this requirement. In particular, in the adhesion of tiles on exterior walls, maintenance of appearance and adhesiveness is required for a long period of time, and this requirement can be met. The adhesive composition of the present invention contains the curable composition, and other components are mixed according to conventional methods as necessary.

[0058] The adhesive composition provided by the present invention contains the curable composition. Therefore, the adhesive composition can exhibit the effects of the curable composition in adhesive applications and can improve adhesion to a topcoat paint. In particular, the adhesive composition can exhibit the effects of the curable composition highly in exterior tile adhesives.

[0059] The curable composition of the present invention can be prepared as a one-component type in which all ingredients are mixed in advance and stored in a sealed state, and then cured by absorbing moisture in the air after application. It can also be prepared as a two-component type in which ingredients such as a curing catalyst, a filler, a plasticizer, and water are mixed separately as a curing agent, and the ingredients are mixed with the polymerizable composition before use. The one-component type is more preferable because it is easy to handle and there is less chance of mixing errors when applying. EXAMPLES

[0060] The present invention will be specifically described below based on examples. Note that the present invention is not limited to these examples. Note that, in the following, "parts" and "%" mean parts by mass and % by mass unless otherwise specified. Methods for analyzing the polymers obtained in the Production Examples, Examples, and Comparative Examples, and methods for evaluating the cured products obtained from the curable compositions are described below.

[0061] <Molecular weight measurement> Using a gel permeation chromatograph (model name "HLC-8320", manufactured by Tosoh Corporation), the number average molecular weight (Mn) and weight average molecular weight (Mw) were obtained in terms of polystyrene under the following conditions. The molecular weight distribution (Mw / Mn) was calculated from the obtained values. Measurement conditions Column: Tosoh TSKgel SuperMultiporeHZ-M x 4 Column temperature: 40℃ Eluent: Tetrahydrofuran Detector: RI

[0062] <Viscosity measurement> The E-type viscosity was measured under the following conditions using a TVE-20H viscometer (salt water / plate method, manufactured by Toki Sangyo Co., Ltd.). Measurement conditions Cone shape: angle 1°34′, radius 24mm (less than 10000mPa·s) Angle 3°, radius 7.7mm (10000mPa s or more) Temperature: 25℃±0.5℃

[0063] <Average number of crosslinkable silyl groups contained in one molecule of component (A)> The number (average number) f of alkoxysilyl groups that are crosslinkable silyl groups was calculated using the following formula from the parts by mass of the monomer having a crosslinkable silyl group when the entire polymer composition was taken as 100 parts by mass. f = (parts by mass of silyl group monomer) / (molecular weight of silyl group monomer) / 100 × Mn (In the formula, Mn is the number average molecular weight of component (A).)

[0064] <Weather resistance test> Each curable composition was applied to a Teflon (registered trademark) sheet to a thickness of 2 mm and cured for one week under conditions of 23°C and 50% RH to produce a cured sheet. The resulting cured product was placed in a metal weather meter (DAIPLA METAL WEATHER KU-R5NCI-A manufactured by DAIPLA WINTES) and subjected to an accelerated weather resistance test. The irradiation conditions were 63°C, 70% RH, and illuminance of 80 mW / cm. 2 The test was carried out for 1500 hours, with a 2-minute shower once every 2 hours. After 1500 hours, the surface condition was visually checked (whether cracks had occurred) and the color difference (△E) was obtained using a color difference meter (Spectrophotometer SE-2000, manufactured by Nippon Denshoku Co., Ltd.), and the weather resistance was evaluated based on the degree of fading. The color difference (△E) was calculated based on the lightness (L * ), red-green chromaticity (a * ) and yellow-blue chromaticity (b * ) was calculated by substituting the value of

[0065]

number

[0066] <Tensile test> Each curable composition was applied to a Teflon (registered trademark) sheet in a thickness of 2 mm and cured for one week under conditions of 23°C and 50% RH to prepare a cured sheet. A dumbbell for a tensile test (JIS K 6251 No. 3 type) was prepared from the obtained cured product, and the breaking elongation and breaking strength were measured at a tensile speed of 200 mm / min using a tensile tester (Autograph AGS-J, manufactured by Shimadzu Corporation).

[0067] <Adhesive strength test> Tests were conducted using mortar boards and exterior mosaic tiles in accordance with JIS A5557 (2006) adhesive strength test method for organic adhesives for exterior tiling. The curable composition was applied to a mortar board (TP Giken, 10 x 50 x 50 mm) in a thickness of about 5 mm, and then drawn with a comb trowel. A commercially available exterior mosaic tile (45 x 45 mm) conforming to the JIS A5209 regulations was then attached. After curing for 4 weeks at 23°C and 50% RH, a special jig was attached to the tile side and the mortar side, and a tensile test was performed at 23°C and a tensile speed of 3 mm / min using a tensile tester (Autograph AGS-J, Shimadzu Corporation) to measure the adhesive strength.

[0068] <Production of Component (A): (Meth)acrylic acid ester copolymer> (Synthesis Example 1) Preparation of (meth)acrylic acid ester copolymer A-1 The temperature of a 1000 mL pressurized stirred tank reactor equipped with an oil jacket was kept at 255°C. Next, while keeping the pressure of the reactor constant, a monomer mixture consisting of 85 parts of n-butyl acrylate (hereinafter referred to as "BA"), 10 parts of tetradecyl acrylate (hereinafter referred to as "TDA"), 5 parts of 3-methacryloxypropyltrimethoxysilane, 10 parts of methyl ethyl ketone (hereinafter referred to as "MEK"), and 2 parts of di-t-butyl peroxide (manufactured by NOF Corp., trade name "Perbutyl D", hereinafter referred to as "DTBP") as a polymerization initiator was continuously fed from a raw material tank to the reactor at a constant feed rate (48 g / min, residence time: 12 min), and a reaction liquid equivalent to the feed amount of the monomer mixture was continuously withdrawn from the outlet. Immediately after the start of the reaction, the reaction temperature once dropped, and then a temperature rise due to the heat of polymerization was observed, but the reaction temperature was maintained at 254 to 256°C by controlling the temperature of the oil jacket. The point at which the temperature stabilized after the start of feeding the monomer mixture was set as the start point for collecting the reaction liquid, and the reaction was continued for 25 minutes from this point, resulting in feeding 1.2 kg of the monomer mixture liquid and recovering 1.2 kg of the reaction liquid. The reaction liquid was then introduced into a thin-film evaporator, and volatile components such as unreacted monomers were separated to obtain vinyl copolymer A-1. The physical properties of vinyl copolymer A-1 are shown in Table 1.

[0069] (Synthesis Examples 2 to 14, Comparative Synthesis Example 1) Except for the changes shown in Table 1 or Table 2, synthesis was performed in the same manner as in Synthesis Example 1. The physical properties of the obtained vinyl copolymer are shown in Table 1 or Table 2.

[0070] [Table 1]

[0071] [Table 2]

[0072] The meanings of the abbreviations shown in Tables 1 and 2 are as follows. BA: n-butyl acrylate HA: 2-ethylhexyl acrylate TDA: Tetradecyl acrylate MMA: Methyl methacrylate TMS: 3-methacryloxypropyltrimethoxysilane DMS: 3-methacryloxypropylmethyldimethoxysilane IPA: Isopropyl alcohol MOA: Methyl orthoacetate MEK: Methyl ethyl ketone DTBP: Di-t-butyl peroxide DTHP: Di-t-hexyl peroxide

[0073] <Preparation and Evaluation of Curable Composition> Examples 1 to 25, Comparative Examples 1 to 3 The (meth)acrylic acid ester copolymer (component (A)), polyoxyalkylene polymer (component (B)), epoxy resin (component (C)) and other raw materials obtained in the above synthesis examples were blended in the ratios shown in Table 3 or Table 4, and mixed for 1 hour using a planetary mixer at 60°C and 10 Torr to obtain curable compositions. The cured products obtained from each composition were subjected to tensile tests, weather resistance tests and adhesive strength tests, and the results are shown in Table 3 or Table 4.

[0074] [Table 3]

[0075] [Table 4]

[0076] The meanings of the abbreviations shown in Tables 3 and 4 are as follows. ES-S3430: Exestar ES-S3430 (a trade name for a polyalkylene oxide having a branched polypropylene oxide main chain and a methyldimethoxysilyl group at each end of the branched chain, number average molecular weight: 16,000, manufactured by AGC) ES-S2420: Exestar ES-S2420 (a trade name for a polyalkylene oxide having a methyldimethoxysilyl group at each end of a linear polypropylene oxide, number average molecular weight: 20,000, manufactured by AGC) jER828: Trade name of bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation) jER806: Trade name of bisphenol F type epoxy resin (manufactured by Mitsubishi Chemical Corporation) jER Cure H30: Trade name of latent epoxy hardener (manufactured by Mitsubishi Chemical Corporation) CCR: Hakuenka CCR (product name of light calcium carbonate, manufactured by Shiraishi Calcium Co., Ltd.) Super SS: Trade name of heavy calcium carbonate, manufactured by Maruo Calcium Co., Ltd. #45: Carbon black product name, manufactured by Mitsubishi Chemical Corporation R820: Tipaque R820 (titanium oxide product name, manufactured by Ishihara Sangyo Kaisha) Tinuvin B75: Trade name of anti-aging agent (manufactured by BASF Japan) U220H: Neostan U220H (a trade name for dibutyltin diacetylacetonate, manufactured by Nitto Kasei Co., Ltd.) S340: Silaace S340 (product name of ketimine-based silane coupling agent, manufactured by JNC Corporation) SZ6300: Trade name of vinyltrimethoxysilane (manufactured by Dow Toray)

[0077] <Interpretation of results> Comparing Examples 9 to 13 with Comparative Example 1, it can be seen that the adhesive strength tends to increase as the number of Si atoms per molecule of component (A) increases, but the flexibility decreases as the elongation decreases. Therefore, it can be seen that by using a component (A) having 1.2 or less Si atoms per molecule, a curable composition with an excellent balance between adhesiveness and flexibility can be obtained. It is noted from Examples 1 to 7 that the higher the molecular weight of component (A), the more the discoloration in the weather resistance test is suppressed and the weather resistance is improved, while the lower the molecular weight of component (A), the lower the viscosity and the better the workability. Therefore, it is understood that by using a component (A) having a weight average molecular weight of 1,000 or more and 50,000 or less, a curable composition excellent in workability as well as weather resistance can be obtained. Comparing Examples 17 to 19, 22, and 23 with Comparative Example 2, it can be seen that, as the blending amount of component (A) increases, discoloration in a weather resistance test is suppressed and weather resistance is improved, but tensile properties (breaking strength, elongation) decrease slightly, resulting in a decrease in flexibility. Therefore, it can be seen that a curable composition with an excellent balance between weather resistance and flexibility can be obtained by blending the amount of component (A) in the range of 20 to 80 parts by mass and the amount of component (B) in the range of 10 to 75 parts by mass (however, the total of components (A), (B), and (C) is 100 parts by mass). Comparing Examples 17 and 20 to 22 with Comparative Example 3, it is seen that as the blending amount of component (C) increases, the adhesive strength increases but the flexibility and weather resistance decrease slightly. Therefore, it is seen that by setting the blending amount of component (C) to 5 to 65 parts by mass (however, the total of components (A), (B) and (C) is 100 parts by mass), a curable composition with an excellent balance of adhesiveness, flexibility and weather resistance can be obtained. [Industrial Applicability]

[0078] The curable composition of the present invention cures at room temperature due to moisture in the air, etc., to give a cured product having excellent adhesive strength, flexibility, and weather resistance. In addition, since the composition has a suitable viscosity, it is also excellent in workability. Therefore, the composition is suitable as a curable composition for adhesion such as an adhesive for exterior tiles.

Claims

1. (A) a (meth)acrylic acid ester copolymer having 0 to 1.2 crosslinkable silyl groups per molecule (provided that the terminal of the molecular chain is represented by the following formula (I) *-S-L 1 -X 1 (I) (In formula (I), S represents a sulfur atom, L 1 represents a divalent linking group, X 1 represents a reactive silyl group, and * represents a bonding position.) (excluding those having a group represented by (B) a polyoxyalkylene polymer having a crosslinkable silyl group, and (C) an epoxy resin having a bisphenol skeleton, The curable composition includes 20 to 80 parts by mass of the component (A), 10 to 75 parts by mass of the component (B), and 5 to 65 parts by mass of the component (C) (wherein the total of the components (A), (B), and (C) is 100 parts by mass).

2. The curable composition according to claim 1, wherein the weight average molecular weight (Mw) of the component (A) is 1,000 or more and 50,000 or less.

3. The curable composition according to claim 1 or 2, wherein the viscosity of the component (A) is from 1,000 mPa·s to 300,000 mPa·s at 25° C.

4. An adhesive composition comprising the curable composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Adhesive composition

    JP2003226854A

  • Curable composition

    JP2004107652A

  • Curable composition

    JP2004124093A

  • Curable adhesive composition

    JP2004323589A

  • Curable resin composition

    JP2019137770A